Recurrence of Fault Valve Behavior in a Continental Collision Area: Evidence From Tilt/Strain Measurements in Northern Adria - Rossi, Giuliana; Pastorutti, Alberto; Nagy, Ildiko; Braitenberg, Carla; Parolai, Stefano (Frontiers in Earth Science, 2021)
We analyzed the data recorded by the NE-Italy subsurface tilt and strainmeter network evidencing a coherent transient signal in the recordings of four tiltmeter sites in the 1984–1990 period that produced a tilt along the main fractures. Borrowing from classical seismology techniques, we used the uprise times to locate the transient signal source. The propagation velocity is compatible with a fluid diffusion process that starts from a source located close to the hypocenter of the February 10, 1983 Uccea earthquake, MD = 4.2 at the Italy-Slovenia border, at an estimated depth of 10.8 km. Our results add to the previous interpretation of a transient signal recorded by several global navigation satellite system (GNSS) stations in the 2006–2009 period in terms of fluid diffusion below the Bovec basin (Slovenia). That source was located upon continuation to the northwest of the Ravne fault, few kilometers to the northeast from the present one, and about 6 km from the July 12, 2004 Bovec–Krn earthquake, Mw = 5.1, depth ~6.1 km. These observations suggest that the area is subject to fault valve behavior episodes that released fluids trapped at depth to the surrounding region as pore-pressure bulges. The convergence between Alpine and External Dinarides structures in this area puts highly permeable dolomitic limestones in contact with low-permeable fine-grained limestones and flysch formations. Therefore, the conditions for overpressure generation can be created, whereas fault movements, from time to time, in close relation with seismic events, can enable fluid diffusion in the surroundings. We also estimated the possible fluid influx needed to maintain overpressure and possible discharge across both the faults. The study provides insights on pore–fluid pressure variations related to slow slip events from a context different from subduction or transform margins, i.e., in a continental collision area.